Orientation of the agarose gel matrix in pulsed electric fields. - Stellwagen, J (1989)
The technique of transient electric birefringence was used to investigate the effect of pulsed electric fields on the orientation of the agarose gel matrix. Orientation of the gel was observed at all electric field strengths. Very slow, time-dependent effects were observed when pulses of 10-100 V/cm were applied to 1% gels for 0.5-2 seconds, indicating that domains of the matrix were being oriented by the electric field. The sign of the birefringence reversed when the direction of the applied electric field was reversed, indicating that the domains tend to orient in the perpendicular direction after field reversal. Theories of gel electrophoresis will need to incorporate the orientation of the matrix in order to provide a complete explanation of electrophoresis in agarose gels.